First reprocessing of Southern Hemisphere ADditional OZonesondes (SHADOZ) profile records (1998–2015): 1. Methodology and evaluation. Issue 12 (19th June 2017) - Witte, Jacquelyn C.; Thompson, Anne M.; Smit, Herman G. J.; Fujiwara, Masatomo; Posny, Françoise; Coetzee, Gert J. R.; Northam, Edward T.; Johnson, Bryan J.; Sterling, Chance W.; Mohamad, Maznorizan; Ogino, Shin‐Ya; Jordan, Allen; et al.
Abstract: Electrochemical concentration cell ozonesonde measurements are an important source of highly resolved vertical profiles of ozone (O3 ) with long‐term data records for deriving O3 trends, model development, satellite validation, and air quality studies. Ozonesonde stations employ a range of operational and data processing procedures, metadata reporting, and instrument changes that have resulted in inhomogeneities within individual station data records. A major milestone is the first reprocessing of seven Southern Hemisphere ADditional OZonesondes (SHADOZ) station ozonesonde records to account for errors and biases in operating/processing procedures. Ascension Island, Hanoi, Irene, Kuala Lumpur, La Réunion, Natal, and Watukosek station records all show an overall increase in O3 after reprocessing. Watukosek shows the largest increase of 9.0 ± 2.1 Dobson Units (DU) in total column O3 ; Irene and Hanoi show a 5.5 ± 2.5 DU increase, while remaining sites show statistically insignificant enhancements. Negligible to modest O3 enhancements are observed after reprocessing in the troposphere (up to 8%) and stratosphere (up to 6%), except at La Réunion for which the application of background currents reduces tropospheric O3 (−2.1 ± 1.3 DU). Inhomogeneities due to ozonesonde/solution‐type changes at Ascension, Natal, and La Réunion are resolved with the application of transfer functions. Comparisons with EP‐TOMS, Aura's Ozone Monitoring Instrument and Microwave Limb Sounder (MLS) satellite O3 overpasses show an overall improvement in agreement after reprocessing. Most reprocessed data sets show a significant reduction in biases with MLS at the ozone maximum region (50–10 hPa). Changes in radiosonde/ozonesonde system and nonstandard solution types can account for remaining discrepancies observed at several sites when compared to satellites. Plain Language Summary: Ozonesondes are point‐source balloon‐borne instruments that measure profiles of ozone, pressure, temperature, and relative humidity from the surface up to 10 hPa ( 30 km). Long‐term ozonesonde data records are relied upon to validate model output and satellite retrievals of ozone, as well as validate their trend calculations. Thus, it is important to have confidence in the quality and accuracy of sonde observations. One way to ensure high quality in the ozonesonde measurement system is to follow the consensus‐based operating procedures and reprocessing guidelines established by ozonesonde experts from around the world. These procedures and guidelines have been adopted by the SHADOZ (Southern Hemisphere ADditional OZonesondes) network. SHADOZ is a NASA/GSFC project in close collaboration with NOAA and other international partners to archive tropical and sub‐tropical ozonesonde data. Since the network started in 1998, 14 stations located north and south of the tropics have archived over 6000 profiles. Like many long‐term observational networks, SHADOZ is characterized by heterogeneous operating procedures, ozonesonde systems, and postprocessing software that impact validation and trend derivation assessments. Reprocessing the SHADOZ ozonesonde data records has led to homogenized data sets that now allow for meaningful comparisons across the network. Key Points: This is the first major reprocessing of SHADOZ ozonesonde data records The effect of reprocessing is observed throughout the profile, and the magnitude of change is highly variable and station dependent Reductions in satellite biases are due to ozonesonde reprocessing techniques that correct for errors in operating procedures